Pemanfaatan WhatsApp dan Zoom Meeting untuk Pembelajaran Daring pada Masa Pandemi Covid-19 di MTs An-Nashihin Kademangan - Hermawati, Lili; Arif, Miftakhul; Marina, Dewi (Ikatan Dai Indonesia, 2022)
This study aims to describe the Utilization of WhatsApp Application Features and Zoom Cloud Meetings as Online Learning Media during the Class IX Covid-19 Pandemic at MTs An-Nashihin Kademangan, inhibiting factors and supporting factors in the use of WhatsApp application features and zoom cloud meetings as online learning media. during the covid-19 pandemic class IX at MTs An-nashihin Kademangan and solutions that were carried out to overcome obstacles that occurred in the use of the whatsapp application features and zoom cloud meetings as online learning media during the covid-19 pandemic class IX at MTs An-Nashihin Kademangan This research was conducted at MTs An-Nashihin Kademangan, South Tangerang City from February 8, 2022 to February 21, 2022. This type of research is qualitative descriptive. The results of the study show that teachers have utilized the WhatsApp application features and zoom cloud meetings to support online learning activities, by utilizing various available features such as photo, video, document, video calls, and video conferencing features. From the results of this study, it is recommended that educators further improve their competence regarding the use of ICT, so that the readiness of learning using technology-based learning can be maximized.